PERAN SATUA BALI DALAM PENGEMBANGAN KOMPETENSI ABAD KE-21 PADA PEMBELAJARAN DI SEKOLAH DASAR - Ida Bagus Yoga Swadnyana, Ida Bagus Yoga Swadnyana; Ni Putu Suci Pramesti, Ni Putu Suci Pramesti; Ni Kadek Emi Agustini, Ni Kadek Emi Agustini; I Gusti Agung Mastri Mahadewi Widyas Putri, I Gusti Agung Mastri Mahadewi Widyas Putri (STKIP Subang, 2026)
This study aims to examine the role of Satua Bali (Balinese traditional oral stories) in developing 21st century competencies in elementary school education. Using a systematic literature review method, this study analyzes peer-reviewed journals, books, and policy documents related to traditional oral literature, 21st century skills, and local wisdom-based education. The findings reveal that Satua Bali contains rich narrative structures that effectively support the development of critical thinking, creativity, communication, and collaboration skills (4Cs), which are the core of 21st century competencies. The integration of Satua Bali in elementary school education serves as a culturally responsive pedagogical approach that simultaneously strengthens students' cultural identity and builds the cognitive and social competencies required in the modern era. Key challenges include limited teacher capacity in utilizing oral literary traditions, the absence of structured curriculum frameworks, and the decreasing familiarity of students with Balinese oral tradition. This study recommends the systematic integration of Satua Bali through projectbased learning, storytelling activities, and character education programs within the Merdeka Curriculum framework.